Β-Galactooligosaccharide in Conjunction With Low FODMAP Diet Improves Irritable Bowel Syndrome Symptoms but Reduces Fecal Bifidobacteria. (20th June 2020) - Wilson, Bridgette; Rossi, Megan; Kanno, Tokuwa; Parkes, Gareth C.; Anderson, Simon; Mason, A. James; Irving, Peter M.; Lomer, Miranda C.; Whelan, Kevin
Abstract : INTRODUCTION: The low FODMAP diet (LFD) reduces symptoms and bifidobacteria in irritable bowel syndrome (IBS). β-galactooligosaccharides (B-GOS) may reduce the symptoms and increase bifidobacteria in IBS. We investigated whether B-GOS supplementation alongside the LFD improves IBS symptoms while preventing the decline in bifidobacteria. METHODS: We performed a randomized, placebo-controlled, 3-arm trial of 69 Rome III adult patients with IBS from secondary care in the United Kingdom. Patients were randomized to a sham diet with placebo supplement (control) or LFD supplemented with either placebo (LFD) or 1.4 g/d B-GOS (LFD/B-GOS) for 4 weeks. Gastrointestinal symptoms, fecal microbiota (fluorescent in situ hybridization and 16S rRNA sequencing), fecal short-chain fatty acids (gas-liquid chromatography) and pH (probe), and urine metabolites ( 1 H NMR) were analyzed. RESULTS: At 4 weeks, adequate symptom relief was higher in the LFD/B-GOS group (16/24, 67%) than in the control group (7/23, 30%) (odds ratio 4.6, 95% confidence interval: 1.3–15.6; P = 0.015); Bifidobacterium concentrations (log10 cells/g dry weight) were not different between LFD and LFD/B-GOS but were lower in the LFD/B-GOS (9.49 [0.73]) than in the control (9.77 [0.41], P = 0.018). A proportion of Actinobacteria was lower in LFD (1.9%, P = 0.003) and LFD/B-GOS (1.8%, P < 0.001) groups than in the control group (4.2%). Fecal butyrate was lower in the LFD (387.3, P = 0.028) and LFD/B-GOS (346.0, P = 0.007) groups than in the control group (609.2). DISCUSSION: The LFD combined with B-GOS prebiotic produced a greater symptom response than the sham diet plus placebo, but addition of 1.4 g/d B-GOS did not prevent the reduction of bifidobacteria. The LFD reduces fecal Actinobacteria and butyrate thus strict long-term use should not be advised.